2021
DOI: 10.3389/fimmu.2021.726747
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Immune Cell Infiltration and Effective Diagnostic Biomarkers in Rheumatoid Arthritis by Bioinformatics Analysis

Abstract: BackgroundRheumatoid arthritis (RA) is a chronic systemic autoimmune disorder characterized by inflammatory cell infiltration, leading to persistent synovitis and joint destruction. The pathogenesis of RA remains unclear. This study aims to explore the immune molecular mechanism of RA through bioinformatics analysis.MethodsFive microarray datasets and a high throughput sequencing dataset were downloaded. CIBERSORT algorithm was performed to evaluate immune cell infiltration in synovial tissues between RA and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 56 publications
1
56
0
Order By: Relevance
“…The synovium is the main target tissue of RA. Several studies reported the hub genes of RA in bioinformatics [ 26 33 ]. These reports also showed that hub genes have a certain diagnostic value in RA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The synovium is the main target tissue of RA. Several studies reported the hub genes of RA in bioinformatics [ 26 33 ]. These reports also showed that hub genes have a certain diagnostic value in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Six datasets were obtained from the Gene Expression Omnibus (GEO) database [ 29 33 ], which were all sampled from the synovium. These datasets are detailed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main function of TCR is to recognize and bind the MHC antigen peptide complex, while CD3 further transfers the signal recognized by TCR into T lymphocytes to induce T lymphocyte activation, and the TCR/CD3 membrane expression level determines the initiation of T lymphocyte activation. Studies have shown that the gene CD247 is also involved in other autoimmune diseases, such as systemic lupus erythematosus [ 16 , 17 ], rheumatoid arthritis [ 18 ], and systemic sclerosis [ 19 ], which shows that CD247 is closely related to the occurrence of autoimmune diseases. The expression of CD247 can affect the development of T cells and lead to abnormal activation of T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For subsequent analysis, we rigorously chose the turquoise module as a candidate module which gains highest correlation coefficient and significant corresponding p value with clinical features among patients suffering Behcet's disease and healthy controls. Recently, a few of studies have comprehensively utilize WGCNA to filtrate synergistically altered gene sets in autoimmune diseases (14)(15)(16)(17)(18). Up till now, amassed structure and function of single protein fragmented our comprehension of their intracellular interactions and pathogenesis pathways.…”
Section: Introductionmentioning
confidence: 99%